2016
DOI: 10.3892/etm.2016.3545
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility, antibacterial activity and characterisation of Enterococcus faecium strains isolated from breast milk

Abstract: Enterococci, which have useful biotechnological applications, produce bacteriocins, including those that exert anti-Listerial activity. The present study aimed to determine the antibiotic susceptibility patterns and antimicrobial activity of Enterococcus faecium strains isolated from human breast milk. The strains were identified using carbohydrate fermentation tests and ribotyping. Subsequently, the antibacterial activity of the isolates was investigated, and the quantities of lactic acid and hydrogen peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In this study, the isolated LAB were screened for potential probiotic activities. Te results of acidity tolerance revealed that all the 60 isolates are tolerant to diferent pH concentrations (2, 3, 4, 5, 6, 7, 8, 9, and 10) as expected for probiotics to have the ability to survive within the varied pH of the intestinal tract, and these results were in agreement with the previous studies which proved that some Enterococcus species can survive in the pH range between 2.0 and 9.5 [29]. Other studies proved that Enterococcus faecium can survive at low pH (1.5 and 3) with the survival rate % between 43 ± 3.0 and 79 ± 4.5 [30], and according to Sanhueza et al [31], some strains of Lactobacillus salivarius can survive for 24 h at pH 2.6.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the isolated LAB were screened for potential probiotic activities. Te results of acidity tolerance revealed that all the 60 isolates are tolerant to diferent pH concentrations (2, 3, 4, 5, 6, 7, 8, 9, and 10) as expected for probiotics to have the ability to survive within the varied pH of the intestinal tract, and these results were in agreement with the previous studies which proved that some Enterococcus species can survive in the pH range between 2.0 and 9.5 [29]. Other studies proved that Enterococcus faecium can survive at low pH (1.5 and 3) with the survival rate % between 43 ± 3.0 and 79 ± 4.5 [30], and according to Sanhueza et al [31], some strains of Lactobacillus salivarius can survive for 24 h at pH 2.6.…”
Section: Discussionsupporting
confidence: 90%
“…MB618 which exhibited resistance to 7, 6, and 5 of the antibiotics used in this study, respectively. This trend was observed by Kıvanç et al [ 56 ] and Reis et al [ 57 ] who reported multiple drug resistance in Enterococcus faecium isolated from human breast milk to ciprofloxacin, ampicillin, gentamicin, penicillin, and vancomycin. Antimicrobial resistance is a complex problem that could be accredited to numerous kinds of mode of transmission and selection pressures [ 58 ].…”
Section: Discussionsupporting
confidence: 66%
“…This opportunistic pathogen, although somewhat less virulent than E. faecalis , is more frequent in vancomycin resistance than E. faecalis and therefore becoming a major threat to public health ( Comerlato et al, 2013 ; Kristich et al, 2014 ). E. faecalis is well-known for its lysozyme resistance, and although not well characterised there are some reports of lysozyme resistant E. faecium strains ( Le Jeune et al, 2010 ; Kivanc et al, 2016 ). The eep -mutants of E. faecium in the present study showed an 8x reduction in lysozyme tolerance compared to the wild type strains.…”
Section: Discussionmentioning
confidence: 99%